Model Of Character Education Development for Ma'had Al Muqoddasah Students Li Tahfizhil Qur'an - Fathony, Mohammad Ro’id; Romadhona, Novia; Iman, Nurul; Katni, Katni,; Arifin, Syamsul (Jurnal Manajemen Pendidikan, 2025)
The character of the santri in society in daily life reflects the mentality and character that has been instilled in life while in the pesantren, especially those related to good morals and personality in accordance with what is in the Qur'an, so it is important to know how model for the development of character education for students at Ma'had Al Muqoddasah Li Tahfizhil Qur'an Nglumpang mlarak Ponorogo. This study uses qualitative research to provide a descriptive description of the model for the development of character education for students. Research location: Ma'had Al Muqoddasah Li Tahfizhil Qur'an Nglumpang Mlarak Ponorogo. Data collection techniques using observation, interviews, and documentation. The data analysis technique is data triangulation, namely by combining data from various aspects to draw conclusions from the results of studying a problem. The results of the study: the model for the development of character education for students at Ma'had Al Muqoddasah Li Tahfizhil Qur'an Nglumpang Mlarak Ponorogo are: a. Muhadloroh, b. Scouting, c. Sports, d. memorizing and simulating the Qur'an, e. Muhadatsah, f. Saturday night discussion, g. Hostel picket and night guard. Implementation of the model for developing character education for students at Ma'had Al Muqoddasah Li Tahfizhil Qur'an Nglumpang Mlarak Ponorogo: a. Well planned. b. Division of tasks according to ability and evaluation. The results of the santri character education development model at Ma'had Al Muqoddasah Li Tahfizhil Qur'an Nglumpang Mlarak Ponorogo: a. Confident, b. Discipline, c. Religious, d. Creative, e. Communicative